Overexpression of ZePrx in Nicotiana tabacum Affects Lignin Biosynthesis Without Altering Redox Homeostasis - García-Ulloa, Alba; Sanjurjo, Laura; Cimini, Sara; Encina, Antonio; Martínez-Rubio, Romina; Bouza, Rebeca; Barral, Luis; Estévez-Pérez, Graciela; Novo-Uzal, Esther; De Gara, Laura; Pomar, Federico (Frontiers in Plant Science, 2020)
Class III plant peroxidases (Prxs) are involved in the oxidative polymerization of lignins. Zinnia elegans Jacq. basic peroxidase (ZePrx) has been previously characterized as capable of catalyzing this reaction in vitro and the role in lignin biosynthesis of several of its Arabidopsis thaliana homologous has been previously confirmed. In the present work, ZePrx was overexpressed in Nicotiana tabacum to further characterize its function in planta with particular attention to its involvement in lignin biosynthesis. Since Prxs are known to alter ROS levels by using them as electron acceptor or producing them in their catalytic activity, the impact of this overexpression in redox homeostasis was studied by analyzing the metabolites and enzymes of the ascorbate-glutathione cycle. In relation to the modification induced by ZePrx overexpression in lignin composition and cellular metabolism, the carbohydrate composition of the cell wall as well as overall gene expression through RNA-Seq were analyzed. The obtained results indicate that the overexpression of ZePrx caused an increase in syringyl lignin in cell wall stems, suggesting that ZePrx is relevant for the oxidation of sinapyl alcohol during lignin biosynthesis, coherently with its S-peroxidase nature. The increase in the glucose content of the cell wall and the reduction of the expression of several genes involved in secondary cell wall biosynthesis suggests the occurrence of a possible compensatory response to maintain cell wall properties. The perturbation of cellular redox homeostasis occurring as a consequence of ZePrx overexpression was kept under control by an increase in APX activity and a reduction in ascorbate redox state. In conclusion, our results confirm the role of ZePrx in lignin biosynthesis and highlight that its activity alters cellular pathways putatively aimed at maintaining redox homeostasis.